How to convince players in construction market? Strategies for effective implementation of circular economy in construction sector. Issue 1 (1st January 2019) - Górecki, Jarosław; Núñez-Cacho, Pedro; Corpas-Iglesias, Francisco Antonio; Molina, Valentín
Abstract: Excessive and progressive industrialization is creating significant economic gaps, whereas large quantities of natural resources are used, and a lot of waste is created. Circular Economy (CE) aims to convert the so-called linear economy paradigm. Changes in legal regulations, business models, and construction methods are necessary for an effective CE implementation. This article aims to attract the attention of key players of the construction sector to a phenomenon of the CE. Basic conditions, a company should meet to perform an effective transformation towards the CE, were described. A hybrid, qualitative-quantitative methodology was used to research. First, a literature review is performed to describe a specificity of the construction industry and features of the construction companies in Poland. Second, a conceptual framework is developed to describe emerging CE business models. Third, a simulation-based analysis is developed to check a propensity of the construction companies to implement the CE and enhance its meaning in different types of economies. Finally, underlying a company's condition as a factor of propensity to implement the CE, it must be noted that stable economies show higher predictability and therefore are more likely to implement principles of the CE than unstable ones. It is concluded that the European Commission should implement new rules, based on promoting closed-loop economy principles, for partnership agreements on the European structural and investment funds in the future. Especially the recommendations given in the article constitute an important contribution of the authors to the development of knowledge about CE in the construction sector.